2011 8th International Conference on Electrical Engineering, Computing Science and Automatic Control 2011
DOI: 10.1109/iceee.2011.6106644
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet analysis of an electrogastrogram database

Abstract: This paper presents the preliminary results of analysis of an electrogastrogram (EGG) database, as well as the procedure of its generation. The visual analysis of the EGG, denoised processes, filtering, wavelet analysis, reconstruction signal and classical parameters obtained are reported. Analysis of the data using these parameters corresponds to previously reported results as well as when they were compared with clinical evaluation. This database could be used in generation of intelligent systems for monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Finally, the results we obtained by evaluating our proposed line length method were superior to the EGG results of previous studies. 9,18,20,26 Although the results obtained by other researchers are promising, they did not compare the FD and GP patient groups to healthy controls. In the literature, some studies have compared FD patients with a healthy group of control subjects 11,19,25,27 and some researchers have compared GP patients with healthy subjects 9,26,31 or stomach cancer subjects.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Finally, the results we obtained by evaluating our proposed line length method were superior to the EGG results of previous studies. 9,18,20,26 Although the results obtained by other researchers are promising, they did not compare the FD and GP patient groups to healthy controls. In the literature, some studies have compared FD patients with a healthy group of control subjects 11,19,25,27 and some researchers have compared GP patients with healthy subjects 9,26,31 or stomach cancer subjects.…”
Section: Resultsmentioning
confidence: 96%
“…Researchers found that the DWT method is useful for extracting EGGs correctly. 9,[19][20][21]26 Furthermore, the line length method reflects the waveform dimensionality variation and is sensitive to changes in the signal amplitude and frequency. Different line length features are calculated from each wavelet sub-signal, which are obtained by passing the EGG signal through a bank of wavelet filters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Classical Fourier domain approaches, [6][7][8][9] like bandpass filters (BPFs) and autoregressive models, have an inherent limitation on their applicability to nonstationary EGG signals whose frequency, amplitude, and phase widely vary across measurement timings and subjects. 5 To circumvent this problem, researchers 10,11 have used wavelets to extract gastric signals amidst severe contaminations from biological artifacts and random noise. Nevertheless, the performance of wavelet denoising crucially depends on the proper selection of mother wavelet.…”
Section: Introductionmentioning
confidence: 99%